2008
DOI: 10.2353/ajpath.2008.071150
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Lipopolysaccharide-Induced Stimulation of the Members of the MAPK Family in Human Monocytes/Macrophages by 4-Hydroxynonenal, a Product of Oxidized Omega-6 Fatty Acids

Abstract: The compound 4-hydroxynonenal (4-HNE) is the major aldehyde formed during lipid peroxidation of -6-polyunsaturated fatty acids and has been suggested to regulate inflammatory responses because it inhibits tumor necrosis factor (TNF) mRNA production in the human monocytic cell line THP-1. Here we demonstrate that 4-HNE inhibits TNF and interleukin-1␤ production in human monocytes in response to lipopolysaccharide. The main action of 4-HNE occurred at the pretranscriptional level; there was no effect on TNF mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 43 publications
2
20
1
Order By: Relevance
“…On the other hand, others have shown that cross-linking of CRIg (or Z39Ig) on human monocytic THP-1 cells causes nuclear translocation of nuclear factor-B and increases expression of matrix metallopeptidase-9 and secretion of IL-8, and that PMA treatment of the human myeloid leukemia cell line TF-1A resulted in increased expression of CRIg. 30 Apart from the substantial differences that exist between normal macrophages and macrophage cell lines, 10 these data are consistent with activation of macrophages via CRIg as crucial for the clearance of complement opsonized microbial pathogens in the absence of a cytokine storm.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…On the other hand, others have shown that cross-linking of CRIg (or Z39Ig) on human monocytic THP-1 cells causes nuclear translocation of nuclear factor-B and increases expression of matrix metallopeptidase-9 and secretion of IL-8, and that PMA treatment of the human myeloid leukemia cell line TF-1A resulted in increased expression of CRIg. 30 Apart from the substantial differences that exist between normal macrophages and macrophage cell lines, 10 these data are consistent with activation of macrophages via CRIg as crucial for the clearance of complement opsonized microbial pathogens in the absence of a cytokine storm.…”
Section: Discussionsupporting
confidence: 67%
“…Monocytes were purified from PBMCs by density gradient centrifugation, as described previously. 9,10 Briefly, PBMCs were washed with RPMI-FCS containing 1 mmol/L EDTA at room temperature. Cells were layered on a 46% iso-osmotic Percoll gradient (GE Healthcare) and spun at 600 ϫ g for 30 minutes at room temperature.…”
Section: Purification Of Cellsmentioning
confidence: 99%
“…Both pro-and anti-infl ammatory activities have been ascribed to glycerophospholipids harboring fragmented and/or oxidized sn -2 fatty acyl groups (59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). Similarly, lyso-PC ( 66,(70)(71)(72)(73)(74) ) and short and/or oxidized fatty acids (75)(76)(77)(78)(79)(80) have been reported to elicit both detrimental and benefi cial responses. In general, in vitro approaches are strategically useful initially, but they have the usual limitations of studies that do not recapitulate essential in vivo features.…”
Section: Lp-pla 2 Expression In Apparently Healthy Subjectsmentioning
confidence: 99%
“…LPS was added to cells at 10 ng/ml final concentration (21). The plate was incubated in 37˚C for 24 h, and the supernatants were harvested for cytokine measurements.…”
Section: Macrophage Stimulation With Lpsmentioning
confidence: 99%